Remote Sensing in Hydrology and Water Management - Schultz, Gert A.; Engman, Edwin T. (Springer Berlin Heidelberg, 2000)
The authors of this book have been approached by consulting engineers: "You know about remote sensing and thus you can obtain hydrological information where no data exist, even without ground measurements, so that I can design the required capacity of a drinking water supply reservoir in a developing country. " On the other hand, the authors have been told: "Remote sensing is not of much use since it is still impossible to estimate ground water resources or surface water flows from remote sensing data. " The major aim of this book is to correct such unjustified illusions as well as exaggerated criticism by providing the reader with sound information on the potential - and the limitations - of remote sensing in the field of hydrology and water management. The book is meant to be a reference and text; it is not a collection of papers from some meeting. The book is intended to provide methods to help the readers solve their own problems in hydrology and water management. Therefore, scientific issues are presented only as far as they are necessary for the application of remote sensing. The reader will see that in some fields, (e. g. evapotranspiration, soil moisture, hydrological modeling) the scientific development is still on the way, while in others operational techniques are already available (e. g. snow melt run off-model, land use classification and detection of land use changes, flood fore casting and control)